Ways to make sunshine - e ([New York] : Bloomsbury Children's Books, 2020)
The Hart family of Portland, Oregon, faces many setbacks after Ryan's father loses his job, but no matter what, Ryan tries to bring sunshine to her loved ones.
Ages 7-10.
Grades 2-3.
Keywords: Family life -- Oregon -- Portland -- Fiction; Schools -- Fiction; African Americans -- Fiction; Portland (Or.) -- Fiction